Pengaruh Pendapatan, Biaya Operasional dan Biaya Distribusi Terhadap Laba Bersih Pada PT. Panca Selaras Medika Periode 2018-2023 - Fitriyani Fitriyani; Muhammad Hasan Ma’ruf; Sri Laksmi Pardanawati (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Abstract. This research aims to determine the effect of income, operational costs and distribution costs on net profit at PT. Panca Selaras Medika for the 2018-2023 period. The population in this research is income statement of PT. Panca Selaras Medika for the 2018-2023 period and after sampling using the saturated sampling method, data on income, operational costs and distribution costs were obtained for 72 months. This type of research is quantitative with the data source used is secondary data seen from the monthly income statement. The data analysis method used is multiple linear regression which consists of descriptive statistical analysis, classic assumption tests, and hypothesis testing using multiple linear regression analysis, F test, t test, and test coefficient of determination. The research results show that income and distribution costs have a positive and significant effect on net profit, while operational costs have a negative and significant effect on net profit.Key word : distribution cost, operational costs, net profit, income